SPackageCreator3D - a 3D content creator to the moodle platform to support human anatomy teaching and learning - Baptista, Fabrício Quintanilha [UNESP]; Neto, Mário Popolin; dos Santos Baglie, Luiz Soares [UNESP]; Weber, Silke Anna Theresa [UNESP]; Brega, José Remo Ferreira [UNESP] (Springer Nature, 2017)
Understanding three-dimensional (3D) forms is very important for anatomy learning. Most methods of anatomy teaching are offered to students through two-dimensional (2D) resources, such as videos and images. In order to support anatomy teaching and learning, many software solutions have been developed to allow the interaction and visualization of 3D virtual models using several techniques and technologies. Even solutions that offer great visual resources lack common teaching and learning environments features. This article aims to present the SPackageCreator3D, a tool to create 3D SCORM packages to the Moodle platform, which is used by a large number of educational institutions, being one of the most popular teaching and learning management platforms, validated by educators and supported by pedagogical a methodology. In order to test the 3D SCORM packages created by the SPackage-Creator3D, an evaluation with 32 students was performed, indicating potential uses and needed improvements.
Keywords: Human anatomy; Moodle; SCORM; Virtual reality